Effect of porosity on mechanical and biological properties of bioprinted scaffolds. Issue 2 (7th October 2022) - Khajehmohammadi, Mehran; Azizi Tafti, Roohollah; Nikukar, Habib
Abstract: Treatment of tissue defects commonly represents a major problem in clinics due to difficulties involving a shortage of donors, inappropriate sizes, abnormal shapes, and immunological rejection. While many scaffold parameters such as pore shape, porosity percentage, and pore connectivity could be adjusted to achieve desired mechanical and biological properties. These parameters are crucial scaffold parameters that can be accurately produced by 3D bioprinting technology based on the damaged tissue. In the present research, the effect of porosity percentage (40%, 50%, and 60%) and different pore shapes (square, star, and gyroid) on the mechanical (e.g., stiffness, compressive and tensile behavior) and biological (e.g., biodegradation, and cell viability) properties of porous polycaprolactone (PCL) scaffolds coated with gelatin have been investigated. Moreover, human foreskin fibroblast cells were cultured on the scaffolds in the in‐vitro procedures. MTT assay (4, 7, and 14 days) was utilized to determine the cytotoxicity of the porous scaffolds. It is revealed that the porous scaffolds produced by the bioprinter did not produce a cytotoxic effect. Among all the porous scaffolds, scaffolds with a pore size of about 500 μm and porosity of 50% showed the best cell proliferation compared to the controls after 14 days. The results demonstrated that the pore shape, porosity percentage, and pore connectivity have an important role in improving the mechanical and biological properties of porous scaffolds. These 3D bioprinted biodegradable scaffolds exhibit potential for future application as polymeric scaffolds in hard tissue engineering applications.